Multiply the polynomial expression (x+2)(x−4) .(2 points)

x2+x+

1 answer

To multiply the polynomial expressions \((x + 2)(x - 4)\), you can use the distributive property (FOIL method):

  1. First terms: \(x \cdot x = x^2\)
  2. Outer terms: \(x \cdot (-4) = -4x\)
  3. Inner terms: \(2 \cdot x = 2x\)
  4. Last terms: \(2 \cdot (-4) = -8\)

Now, combine all these results:

\[ x^2 - 4x + 2x - 8 \]

Combine like terms:

\[ x^2 - 2x - 8 \]

So, the result of multiplying \((x + 2)(x - 4)\) is:

\[ x^2 - 2x - 8 \]